Affiliate marketing and intention to adopt mudarabah: The mediating role of trust in Islamic financial decision-making - Qisty Amalina Rusmana Putri; Fasiha Fasiha; Muh. Rasbi (Universitas Islam Malang, 2024)
The adoption of mudarabah, an Islamic financial instrument that relies on moral integrity and transparency rather than collateral, fundamentally depends on trust. In this context, the increasing use of digital strategies such as affiliate marketing may influence both trust formation and financial decision-making. However, the relationship between trust in Islamic economic practices and affiliate marketing remains underexplored despite its growing relevance. By examining how affiliate marketing affects people's intentions to adopt mudarabah behaviors and highlighting the mediation role of trust, this study addresses a critical gap. Using a quantitative explanatory approach, data were collected from 155 respondents who met the criteria of having prior exposure to Islamic financial products and experience in engaging with social media platforms, through an online survey. The relationships between the constructs were examined using partial least squares structural equation modeling. The findings show that the intentions of individuals to get involved in mudarabah are directly and significantly impacted by affiliate marketing, with trust acting as a crucial mediating factor. This emphasizes how crucial it is for marketing initiatives to establish trust through openness, truthfulness, and unambiguous communication. Affiliates who clearly disclose their partnership with financial institutions, present accurate information about expected returns, and openly explain the risks involved in mudarabah investments are more likely to earn the trust of investors and encourage engagement with Islamic-compliant financial products.